2020
DOI: 10.3389/fonc.2020.00464
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Deep Learning Radiomics Model Predicting Lymph Node Status in Operable Cervical Cancer

Abstract: Aim: To develop and validate a deep learning radiomics model, which could predict the lymph node metastases preoperatively in cervical cancer patients. Conclusion: This study used deep learning method to provide a comprehensive predictive model using preoperative CT images, tumor histology, and grade in cervical cancer patients. This model showed an acceptable accuracy in the prediction of lymph node status in cervical cancer. Our model may help identifying those patients who could benefit a lot from radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
(35 reference statements)
1
18
1
Order By: Relevance
“…Despite nomogram's visualization, it has limited power for future big data era. On the contrary, deep learning is like a "black box", its development trend is inevitable and more conducive to the analysis of big data (23). In this study, we found no significant difference in terms of AUCs between the clinical-LR and clinical-DNN models.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Despite nomogram's visualization, it has limited power for future big data era. On the contrary, deep learning is like a "black box", its development trend is inevitable and more conducive to the analysis of big data (23). In this study, we found no significant difference in terms of AUCs between the clinical-LR and clinical-DNN models.…”
Section: Discussioncontrasting
confidence: 62%
“…Dong et al. ( 23 ) recently compared the DNN model, LR and SVM to predict lymph node status in operable cervical cancer, and they also found that DNN performed best. Bibault et al.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics has been involved in many aspects of cervical cancer, including prediction of tumor staging (21,22), histological grading (23,24), lymphovascular space invasion (LVI) (25), LNM (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36), treatment response (37)(38)(39)(40)(41)(42), and outcome (43)(44)(45)(46)(47)(48) based on multimodal imaging tools (e.g., CT, MRI, and PET/CT). In clinical practice, the issues of most concern may be the evaluation of LNM, treatment response, and survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The organic integration of big data technology and medical image-assisted diagnosis has promoted the emergence of a new imaging method, that is, radiomics [ 14 16 ]. By extracting massive features from images and capturing potential intra-tumour heterogeneity to predict treatment response, radiomics can effectively solve the problem of difficulty in quantitative evaluation of tumour heterogeneity and guide the formulation of personalised treatment plans [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%